Multi-terminal flexible DC grid circuit breaker withstands multi-lightning strike analysis - Yutao Tang; Hongchun Shu; Kai He; Yue Dai; Yu Kuang; Yiming Han; Weijie Lou (Scientific Reports)
Abstract Lightning represents the primary threat to power grids, with approximately 80% of natural occurrences being multi-lightning strikes, which have been extensively studied and confirmed to pose even more severe hazards. Hybrid DC circuit breakers (DCCBs) exhibit promising application prospects due to their superior interruption performance. During multi-lightning strikes, lightning intrusive waves pose a greater threat to the insulation of equipment such as hybrid DC fuses, fast mechanical switches, and insulated gate bipolar transistors. Therefore, this paper establishes a simulation model using the Real-Time Digital Simulator based on the model and parameters of the DCCB in the ± 500 kV Zhangbei HVDC project in China. It analyzes the lightning intrusive waves on the DCCB and investigates the energy absorption of metal oxide varistors (MOVs) in the energy-consuming branch of the DCCB under multi-lightning strikes, as well as the overvoltage levels of various branches of the DCCB under such conditions. The research results indicate that the energy-consuming branch has a certain tolerance to multi-lightning strikes. However, if the MOV collapses under multi-lightning strikes, it can lead to severe overvoltage issues. Therefore, the design and selection of DCCBs should fully consider the impact of multi-lightning strikes.